Synthesis of zeolite from coal fly ash by fusion method / Zulkifli. A. B ... [et al.] - A.B, Zulkifli.; F.S, Mohd Jufri; M.A.M, Mohamad Sobri.; N.H, Abdul Rani; A.S.A.K, Sharifah (2018)
Coal fly ash has been regarded as waste and are typically produced in large quantities in power plants. However, not many know that it can be used for the synthesis of zeolites. Zeolites are known for its porous characteristic that helps in absorbing charged ions. In this report, the synthesis of zeolite from coal fly ash using fusion method was studied. The synthesis was made by mixing coal fly ash with Sodium Hydroxide (NaOH). Sodium Hydroxide (NaOH) are used to produce NaP type zeolite. The parameters used were temperature (80"C, IO0'C, 120'C, and 140'C), molarity of sodium hydroxide (2M, 4M, and 6M) and the reaction time is 6 hours. The samples are then characterized using Fourier-transform infrared spectroscopy (FTIR) and Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). Pb2+ was being used as heavy metal sample for the ICP-OES testing. The absorption test shows that the highest absorption was by using a sample with the parameter of 140'C temperature and 4M NaOH molarity with 84.36% Pb2+ removal percentage. However, it can also be seen that I00c samples have an increasing Pb2+ removal percentage as the molarity used increases. This proves that l00'C is the optimum temperature for synthesis of zeolite using fusion method. For comparison, a commercial zeolite was also tested in Pb2+ removal.